TRANSFORMATIONS OF THE EARTH MATTER AS A RESULT OF THE ENERGY EXCHANGING PROCESSES - ORYSHCHENKO, I. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
There are considered the correlations between potential and kinetic energy and their influence upon condition matter. Fluctuation the energy condition surrounding outer space changes the external energy exchange of Earth and may be a cause of the global climatic variations our planet.